COPD inhaled drug therapy in primary health care: an integrated view - Costa, Rodrigo (2023)
COPD is a chronic disabling disease with persistent respiratory symptoms and airflow limitation. It is frequently related to comorbidities that must be managed in an integrated way. Inhalation therapy is the therapy of choice for the treatment of COPD patients. When monotherapy is chosen, long-acting anticholinergics should be preferred. Dual bronchodilation is the most appropriate baseline treatment for most patients with COPD. Triple therapy is required for a subpopulation of these patients, and general practitioners/family doctors must be qualified to prescribe it. Teaching and regular assessment of inhalation techniques are key to therapeutic success. The adoption of the acronym EDUCAR (Explain, Demonstrate, Use, Correct, Annotate, Reassess) is proposed to be applied in all appointments of people using inhaled therapy to achieve the greatest benefit for the patient.